Protease-activated receptor 2 protects against myocardial ischemia-reperfusion injury through the lipoxygenase pathway and TRPV1 channels - Zhong, Beihua (Exp Ther Med, 2019)
This study tests the hypothesis that the lipoxygenase (LOX) pathway mediates protease-activated receptor (PAR) 2-induced activation of the transient receptor potential vanilloid receptor 1 (TRPV1) to protect the heart from ischemia/reperfusion (I/R) injury. SLIGRL, a PAR2 activating peptide, was administered prior to reperfusion following left anterior descending coronary artery ligation in wild type (WT) and TRPV1 knockout (TRPV1(−/−)) mice. In a Langendorffly perfused heart I/R model, hemodynamic parameters, including left ventricular end-diastolic pressure, left ventricular developed pressure, coronary blood flow and left ventricular peak +dP/dt were evaluated after I/R. SLIGRL reduced the cardiac infarct size in WT and TRPV1(−/−) mice with a greater effect in the former strain (P<0.05). SLIGRL increased plasma levels of calcitonin gene-related peptide (CGRP) and substance P in WT (both P<0.05) but not in TRPV1(−/−) mice. Pretreatment with CGRP8-37 (a CGRP receptor antagonist) or RP67580 (a neurokinin-1 receptor antagonist) alone had no effect on SLIGRL-induced cardiac protection in either strain. However, combined administration of CGRP8-37 and RP67580 abolished SLIGRL-induced cardiac protection in WT but not in TRPV1(−/−) mice. Nordihydroguaiaretic acid (a general LOX inhibitor) and baicalein (a 12-LOX inhibitor), but not indomethacin (a cyclooxygenase inhibitor) and hexanamide (a selective cytochrome P450 epoxygenase inhibitor), abolished the protective effects of SLIGRL in WT (all P<0.05) but not in TRPV1(−/−) hearts. These data suggested that PAR2, possibly via 12-LOX, activates TRPV1 and leads to CGRP and substance P release to prevent I/R injury in the heart, indicating that the 12-LOX-TRPV1 pathway conveys cardiac protection to alleviate myocardial infarction.